Ferula ermenekense (Apiaceae), an interesting new species from Southern Anatolia in the eastern Mediterraenean Basin - Sağiroğlu, Mehmet; Duman Hayri̇ (Phytotaxa, 2023)
Ferula ermenekense is described and illustrated as a new species from Karaman province in South Anatolia, Turkey. Ferula ermenekense is morphologically close to F. lycia, F. duranii and F. pisidica. In this study, the diagnostic morphological features, distribution, conservation status, habitat and ecological characteristics of the new species are discussed. Micromorphological characteristics of F. ermenekense, F. lycia, F. duranii and F. pisidica mericarps are also examined and compared by using LM and SEM analyses.